2008
DOI: 10.1080/03052150802043681
|View full text |Cite
|
Sign up to set email alerts
|

An interval full-infinite programming method to supporting environmental decision-making

Abstract: An interval full-infinite programming (IFIP) method is developed by introducing a concept of functional intervals into an optimization framework. Since the solutions of the problem should be 'globally' optimal under all possible levels of the associated impact factors, the number of objectives and constraints is infinite. To solve the IFIP problem, it is converted to two interactive semi-infinite programming (SIP) submodels that can be solved by conventional SIP solution algorithms. The IFIP method is applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Different from a single interval, e.g., [a, b], with deterministic bounds a and b, a dual interval [[a, c], [d, b]] carries interval bounds [a, c] and [d, b], representing the uncertainties in lower and upper bounds of a single interval. Recently, a number of similar studies were reported on dealing with uncertainties in the boundaries of a single interval (Guo et al, 2008;He et al, 2008He et al, , 2009Lu et al, 2008). Nie et al (2007) introduced a concept of fuzzy-boundary interval (an interval with fuzzy-valued lower and upper bounds) and then developed an interval-parameter fuzzy robust programming (IFRP) model.…”
Section: Introductionmentioning
confidence: 98%
“…Different from a single interval, e.g., [a, b], with deterministic bounds a and b, a dual interval [[a, c], [d, b]] carries interval bounds [a, c] and [d, b], representing the uncertainties in lower and upper bounds of a single interval. Recently, a number of similar studies were reported on dealing with uncertainties in the boundaries of a single interval (Guo et al, 2008;He et al, 2008He et al, , 2009Lu et al, 2008). Nie et al (2007) introduced a concept of fuzzy-boundary interval (an interval with fuzzy-valued lower and upper bounds) and then developed an interval-parameter fuzzy robust programming (IFRP) model.…”
Section: Introductionmentioning
confidence: 98%
“…An effective way of describing this uncertainty would be the functional intervals; this can be defined as a lower and an upper bound, which are both functions of its associated impact factor. When the coefficients of the objective functions and constraints are both allowed to be functional intervals and/or intervals, the ordinary linear programming problem becomes a more complicated problem [11,42,14,15,44,45]. Thus, interval full-infinite programming (IFIP) can be generated by introduced full-infinite programming (FIP) into an interval linear programming (ILP) framework.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental protection and resources conservation are of major concerns along with increasing waste generation and decreasing waste-disposal capacity. In response to these, various optimization techniques were used for supporting effective management of the systems (Chang and Wang, 1997;Huang et al, 2007;Ahluwalia and Nema, 2007;Li, 2007;He et al, 2008). At the same time, uncertainties exist in many system components (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, incorporation of the joint probabilistic constraint programming (JPC) method and the dual-interval concept within an interval linear programming framework would be helpful for reflecting such dual uncertainties. Although several approaches were reported on dealing with uncertainties in the boundaries of interval inputs (Cai et al, 2007;Nie et al, 2007;Guo et al, 2008;Lu et al, 2008;He et al, 2008), limitations existed when the quality of information was not satisfactory enough to be presented as probability and/or possibility distributions for the boundaries. Few previous reports could be found on the development of a hybrid inexact probabilistic model that can simultaneously handle joint probabilistic constraints and dual uncertainties.…”
Section: Introductionmentioning
confidence: 99%